Occurence and seasonal variations of helminth parasites of bovines in the Itaju do Colônia Region - Itapetinga pastoral agrosystem - Santana, José Carlos R. (2014)
ln the periods from January to December, 1980, and May to April 1982, helminth parasites of bovines were surveyed through monthly feces analyses (EPG), cultures from feces (LPG) and necropsies in the Itaju do Colômbia Region - Itapetinga Pastoral Agrosystem. Means of EPG were high at the begining of each experimental period, diminishing in the third month onwards. Cultures from feces samples showed a predominance of Cooperia spp and Haemonchus spp larvae. Forty-eight calves four to five months old were necropsied and from the total of adult worms recuperated a high percentage (75,25%) was for the Cooperia genus and 17,63% of Haemonchus. The other genus represented only 8% of the total. The species identified were: Cooperia panctata, Haemonchus similis, Oesophagostomum radiatum, Haemochus contortus, Bunostomum phlebotomum, Trichurisspp, Dictyocaulus viviparus, Agriostorum wryburgi, Trichostrongylus axei, Trichostrongylus colubrifonnis e Cooperia pectinata. During the second experimental period bigger quantities of adult worms recuperated from the necropsies were observed, independently of the influence of rainfall and temperature of the worms population.